Automated hybrid closed‐loop control with a proportional‐integral‐derivative based system in adolescents and adults with type 1 diabetes: individualizing settings for optimal performance. Issue 5 (18th May 2016) - Ly, Trang T.; Weinzimer, Stuart A.; Maahs, David M.; Sherr, Jennifer L.; Roy, Anirban; Grosman, Benyamin; Cantwell, Martin; Kurtz, Natalie; Carria, Lori; Messer, Laurel; von Eyben, Rie; Buckingham, Bruce A.
Abstract: Background: Automated insulin delivery systems, utilizing a control algorithm to dose insulin based upon subcutaneous continuous glucose sensor values and insulin pump therapy, will soon be available for commercial use. The objective of this study was to determine the preliminary safety and efficacy of initialization parameters with the Medtronic hybrid closed‐loop controller by comparing percentage of time in range, 70–180 mg/dL (3.9–10 mmol/L), mean glucose values, as well as percentage of time above and below target range between sensor‐augmented pump therapy and hybrid closed‐loop, in adults and adolescents with type 1 diabetes. Methods: We studied an initial cohort of 9 adults followed by a second cohort of 15 adolescents, using the Medtronic hybrid closed‐loop system with the proportional‐integral‐derivative with insulin feed‐back (PID‐IFB) algorithm. Hybrid closed‐loop was tested in supervised hotel‐based studies over 4–5 days. Results: The overall mean percentage of time in range (70–180 mg/dL, 3.9–10 mmol/L) during hybrid closed‐loop was 71.8% in the adult cohort and 69.8% in the adolescent cohort. The overall percentage of time spent under 70 mg/dL (3.9 mmol/L) was 2.0% in the adult cohort and 2.5% in the adolescent cohort. Mean glucose values were 152 mg/dL (8.4 mmol/L) in the adult cohort and 153 mg/dL (8.5 mmol/L) in the adolescent cohort. Conclusions: Closed‐loop control using the Medtronic hybrid closed‐loop system enables adaptive, real‐time basal rate modulation. Initializing hybrid closed‐loop in clinical practice will involve individualizing initiation parameters to optimize overall glucose control.